Pembelajaran Geografi Berbasis Investigasi dan Turnamen Pada Siswa Kelas X SMA Negeri 3 Takalar - Syarif, Erman (UNIVERSITAS NEGERI MAKASSAR, 2018)
This study aims to determine differences in student learning outcomes in Geography subjects through the application of investigative learning models and tournaments on the subject matter of atmospheric dynamics and their impact on life. This research is an experimental research. The population is class X students consisting of 8 classes. Sampling with cluster random sampling technique. The sample in this study is class XI 3 as an experimental class and class X 7 as a control class. The results showed that the average value of learning outcomes through the application of investigative learning models was 64.27 of 48 students while the average value of student learning outcomes through the implementation of tournament learning models reached 81.56 of the total number of 48 students . Based on the calculation results it can be concluded that the learning outcomes of geography students who use the tournament learning model are better than the learning outcomes of students who use the investigation model especially on the subject of the environment and its preservation. Therefore it is recommended: (1) teachers can use various learning methods in the learning process to improve student learning outcomes, (2) for teachers who do not understand about learning models, training should be given, and (3) for students who have low interpersonal intelligence teachers can use learning models as an alternative method in the learning process.